Cerebellar encephalitis associated with anti-mGluR1 antibodies: a case report and comprehensive literature review - Chen, Xue; Chen, Yanan; Di, Lu; Liu, Na; Liu, Ting; Cai, Yun; Di, Weiying (Frontiers in Neurology, 2024)
Anti-metabotropic glutamate receptor 1 encephalitis is an uncommon autoimmune condition characterized by a subacute onset of cerebellar syndrome. Frequently, it also manifests as sleep disorders and cognitive or behavioral changes. While immunotherapy is the primary treatment approach, the disease remains poorly understood. Herein, we present a case of anti-metabotropic glutamate receptor 1 encephalitis, highlighting its primary cerebellar syndrome manifestation. The first magnetic resonance imaging scan showed no obvious abnormality. Lumbar puncture showed increased cerebrospinal fluid pressure, increased white blood cell count and protein level. The next-generation sequencing of cerebrospinal fluid showed Epstein–Barr virus infection, and the patient was diagnosed with viral cerebellar encephalitis. However, antiviral therapy was ineffective. Finally, anti-metabotropic glutamate receptor 1 was measured at 1:1,000, and the patient was definitely diagnosed with anti-metabotropic glutamate receptor 1 encephalitis. Therefore, clinicians should pay attention to such diseases to avoid misdiagnosis.